Buck’s Fascia in Addition to Dartos Fascia is an Effective Intermediate Layer in Repair of Hypospadias - Sulochana Dahal, Bibhushit Mahat, Nadir Hussain, Muhammad Saleem, Ubaid-ur-Rahman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Being a common congenital urogenital disorder, hypospadias is mostly treated by Snodgrass urethroplasty; urethrocutaneous fistula is the most frequent complication. Objective: To assess the outcomes of Snodgrass Urethroplasty when Buck’s (external spermatic) fascia was used with Dartos fascia to interpose between the neourethra and skin and to compare the results when only Dartos fascia was applied. Study Design: Prospective comparative study Place and Duration of Study: Department of Pediatric Surgery, Children’s Hospital & Institute of Child Health, Lahore Pakistan from 1st September 2018 to 31st August 2019 Methodology: Seventy four patients who were randomly divided into two groups. Group 1 who underwent Snodgrass urethroplasty with dartos fascia as intermediate layer; while both dartos & buck’s fascia was used in Group 2. Post-operative results were compared in terms of urethrocutaneous fistula, meatal stenosis and wound dehiscence. Results: Eleven patients with urethrocutaneous fistula, the rate of urethrocutaneous fistula was significantly less in the Buck’s and Dartos group [2(5.4%) versus 9(4.3%) in the dartos only group; p=0.022]. 4 patients presented with meatal stenosis; 3 (8.1%) from dartos group and 1 (2.7%) from dartos and buck’s group. 5 patients presented with Wound dehiscence; 4 (10.8%) from control group and 1 (2.7%) from experimental group, both of which were not statistically significant (p-value 0.304 and 0.165 respectively). Conclusion: The use of Buck’s Fascia in addition to Dartos Fascia as an interpositional layer in hypospadias repair bears immense role in the prevention of the most common complication i.e. urethrocutaneous fistula. Keywords: Buck’s fascia, Dartos fascia, Hypospadias, Urethrocutaneous fistula